Here slope is -2
and intercept is 4
so equation is
-2 x+4
if u have any doubt ask me
please mark as brainliest
Answer:
It takes 1 seconds for push-ups and 3 seconds for sit-ups for Mei to do exercise.
Step-by-step explanation:
Given:
Let the time taken for push-ups be 'x'.
Let the time taken for sit-ups be 'y'.
Now Given:
17 push-ups and 6 sit-ups, it takes a total of 35 seconds.
So we can say that;
![17x+6y=35 \ \ \ \ equation \ 1](https://tex.z-dn.net/?f=17x%2B6y%3D35%20%5C%20%5C%20%5C%20%5C%20equation%20%5C%201)
Also Given:
41 seconds to do 20 push-ups and 7 sit-ups.
so we can say that;
![20x+7y=41 \ \ \ \ equation \ 2](https://tex.z-dn.net/?f=20x%2B7y%3D41%20%5C%20%5C%20%5C%20%5C%20equation%20%5C%202)
Now Multiplying equation 1 by 7 we get;
![7(17x+6y)=35\times7\\\\119x+42y= 245 \ \ \ \ equation \ 3](https://tex.z-dn.net/?f=7%2817x%2B6y%29%3D35%5Ctimes7%5C%5C%5C%5C119x%2B42y%3D%20245%20%5C%20%5C%20%5C%20%5C%20equation%20%5C%203)
Now Multiplying equation 2 by 6 we get;
![6(20x+7y)=41\times6\\\\120x+42y = 246 \ \ \ \ equation\ 4](https://tex.z-dn.net/?f=6%2820x%2B7y%29%3D41%5Ctimes6%5C%5C%5C%5C120x%2B42y%20%3D%20246%20%5C%20%5C%20%5C%20%5C%20equation%5C%204)
Now Subtracting equation 3 from equation 4 we get;
![120x+42y-(119x+42y)=246-245\\\\120x+42y-119x-42y=1\\\\x=1\ sec](https://tex.z-dn.net/?f=120x%2B42y-%28119x%2B42y%29%3D246-245%5C%5C%5C%5C120x%2B42y-119x-42y%3D1%5C%5C%5C%5Cx%3D1%5C%20sec)
Now substituting the value of x in equation 1 we get;
![17x+6y=35\\\\17\times1+6y=35\\\\17+6y=35\\\\6y=35-17\\\\6y= 18\\\\y=\frac{18}6 = 3\ seconds](https://tex.z-dn.net/?f=17x%2B6y%3D35%5C%5C%5C%5C17%5Ctimes1%2B6y%3D35%5C%5C%5C%5C17%2B6y%3D35%5C%5C%5C%5C6y%3D35-17%5C%5C%5C%5C6y%3D%2018%5C%5C%5C%5Cy%3D%5Cfrac%7B18%7D6%20%3D%203%5C%20seconds)
Hence It takes 1 seconds for push-ups and 3 seconds for sit-ups for Mei to do exercise.
Answer:
531.4
Step-by-step explanation:
ED/AE=BC/AB
ED=AE*BC/AB
ED=240*620/280
ED=531.4
Answer:
16d^20
Step-by-step explanation:
to raise a product to a power, raise each factor to that power. (-2)^4x(d^5)^4
evaluate the power (-2)^4 x (d^5)^4
16 x (d^5)^4